Hukum Penundaan Pembagian Harta Warisan Produktif Perspektif Al-Mashlahah Al-Mursalah - Zainal Muttaqin (At-Tafkir, 2023)
This study discusses the law of delaying the distribution of productive inheritance which is analyzed with the requirements of al-mashlahah al-mursalah using library research methods with descriptive qualitative analysis techniques to describe why the distribution of productive inheritance can be postponed and how to determine and distribute profits from asset management productive inheritance to each heir. The research results reveal that: 1). The distribution of productive inheritance is legal to postpone as long as it is agreed by all heirs because the benefits to be achieved in delaying the distribution do not conflict with texts and ijma', belonging to the two types of maqasid al-shari'ah which protect the heir's descendants from economic weaknesses and preserve assets. heirs to continue to be productive, benefit from the development of their wealth something real, and generally applicable that impacts the family as the important unit in society; 2). Profits from productive inheritance which belong to all heirs (owners of capital) are distributed to each heir in accordance with the amount of the level of each share according to fiqh al-mawaris. Postponement and development of productive inheritance is important to be agreed upon by the heirs for the benefit of the family's economic welfare.